KEPATUHAN WARTAWAN TERHADAP KODE ETIK JURNALISTIK DI KOTA PALANGKA RAYA - Rachmat Hidayat; Idiannor Mahyudin; Mardiana Mardiana (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2014)
Each of Indonesian journalists must uphold the Code of Journalistic Ethics in carrying out any work in the field of journalism . However, this time not all Indonesian journalists make journalism ethics as a " crown " in the works . A reliable and professional journalists should have the following three criteria . First , master the skills of journalism . Second , control of field coverage. Third , understand and adhere to journalistic ethics .For that purpose made a post this time to find out what things are often a problem in the world of journalism ethics , so that could be a picture of good press and imaging and uphold the rules of the world press .The world press is also closely related to the world of communication and now it often becomes a problem due to a communication error is in disseminating information to the public , so the performance issues of the press in this case journalists interesting to do in-depth study on the ethics of their work to avoid errors chaos in the world of communication or communication that result in harm to others .The method used Relating to this study , the approach used in this study is using a qualitative approach using sychronization source of primary data and secondary data sources . Sources of primary data obtained through interviews to journalists as press personnel who perform journalistic tasks and conduct field observations , while secondary data sources which include regulations , code of conduct , official documents . books and reports the results of research in the form of secondary data material in this study .The results of this scientific journals can be proved with some interviews to journalists in Palangkaraya who admits that they can not work and understand 100 percent implementation of the code of journalistic ethics , particularly the clauses relating to the independence of the press to do the job .The conclusion in the press itself still needs some improvement in addition to providing training to journalists but also strengthen the structure and capabilities of the institution itself in the Indonesian press . Key Word : Obedience, Ethic Code, Journalism